Wybrane aspekty realizacji portalu korporacyjnego w organizacji gospodarczej - Dudycz, Helena (Selected problems of the enterprise information portal's implementation, 2006)
The aim of the article is the analysis of the enterprise information portal’s implementation. The in-crease of the portal’s realization exists both in the world and in Poland. That’s why important thing is research of the reasons of portal’s implementation and economical aspects of this IT project. The first part briefly characterizes circumstances of the realization portal. Then the economical aspects of implementation IT projects are presented. The last part of the paper contains the problems’ description of the effectiveness of the portal’s realization.
Prace Naukowe Akademii Ekonomicznej we Wrocławiu; 2006; nr 1134, s. 304-312